Candida dubliniensis: An update - SULLIVAN, DEREK; SHANLEY, DIARMUID; MCCARTAN, BERNARD; MORAN, GARY; COLEMAN, DAVID (My University, 1999)
The increased incidence of fungal infections during the last decade has been well-documented. Given that one of the most important factors contributing to this phenomenon is the increased numbers of immunocompromised individuals, it is perhaps not surprising that species previously not associated with human disease and novel species previously unknown to science have been identified as potential pathogens (e.g., Penicillium marneffei , Emmonsia pasteuriana and Candida dubliniensis).
PUBLISHED
Keywords: Dental Science; Microbiology; Candida dubliniensis; Genes & Society; Immunology, Inflammation & Infection